Chemical oxygen demand and nitrogen removal from real membrane-manufacturing wastewater by a pilot-scale internal circulation reactor integrated with partial nitritation-anammox. (November 2022) - Fan, Yuqin; Tan, Xinwei; Huang, Yong; Hao, Tianwei; Chen, Hong; Yi, Xue; Li, Dapeng; Pan, Yang; Li, Yong; Kong, Zhe
Graphical abstract: Highlights: The IC-PN/A succeeded in the long-term treatment of high-strength MMW. The entire IC-PN/A system obtained a total COD removal efficiency of over 85%. More than 90% TN removal efficiency can be obtained with 150% reflux ratio. The parameters such as DO, FA and NH4 + are controlled to obtain stable NiAE. This study is the first report of a pilot-scale IC-PN/A system for MMW. Abstract: A pilot-scale system integrating internal circulation and partial nitritation-anammox successfully treated real high-strength membrane-manufacturing wastewater in this study. With this pilot-scale system, a high chemical oxygen demand (COD) removal efficiency of 85 % and a nitrogen removal of 90 % are achieved at an organic loading rate of 6.0 kg COD/m 3 /d. The nitrogenous organic matters in the internal circulation zone are degraded into ammonia nitrogen. In the partial nitrification zone, nitrite accumulation is achieved, providing a suitable NH4 + -N/NO2 − -N ratio for anammox reaction. Partial nitritation is achieved by maintaining an operational temperature at 30–35 °C, free ammonia concentration at 5–7 mg/L and dissolved oxygen at 0.4–0.7 mg/L with a reflux ratio of 150 %. The COD to nitrogen ratio in the internal circulation effluent is maintained below 3.0 to inhibit nitrite oxidizing bacteria. This study demonstrates that a pilot-scale system can efficiently remove organic matters and nitrogen from wastewater of membrane-manufacturing industry.